An in vitro inhibition of human malignant cell growth of crude water extract of cassava (Manihot esculenta Crantz) and commercial linamarin - Nashiru Billa; Nasir Umar-Tsafe; Nurhafizah Abdullah; Umar F. Yusuf; Rozita Rosli; Sunny E. Iyuke; Fakhru'l-Razi Ahmadun (Songklanakarin Journal of Science and Technology (SJST), 2006)
Epidemiological studies had shown a link between low incidences of cancer in communities where cassava intake is the main staple. The prophylactic action of cassava intake and its deleterious effect on humans are attributed mainly to the expressed toxicity of the aglycone moiety of the cyanogenic glucoside linamarin, when the latter breaks down. The effect of crude water extract of cassava leaf and that of commercial linamarin was investigated on two human tumor cell lines Caov-3 (ovarian), and HeLa (cervical adenocarcinoma) in vitro, using the MTT- assay for cell growth inhibition/cytotoxicity. The effect of the enzyme linamarase (EC 3.2.1.21), a β-glucosidase also tapped from the cassava plant and treated appropriately was tested on one of the cell lines. Crude water extract or commercial linamarin was added in a final concentration of 300 µg/ml with or without the partially purified enzyme (10% added of total cell volume and culture medium) to the seeded cells. The water extract was more efficacious, eliciting an IC50 value of 38 µg/ ml and 57 µg/ml, respectively, for the ovarian and cervical cell lines, while the commercial linamarin shows a growth inhibition of 150 and 210 µg/ml, respectively, for the two cell lines. Inclusion of the enzyme on a linamarin treated cervical cell line improved the growth inhibition to 40 µg/ml. The antineoplastic effect exhibited by the two samples containing the cyanogenic glucoside is explained in terms of the activity of endogenous/exogenous linamarase, presence of dietary factors in the crude extract, and a possibly induced bystander effect. Tumors are unlikely to develop any resistance against hydrocyanic acid, due to its inhibitory role in oxidative phosphorylation. Additionally, an inbuilt mechanism in vivo ensures detoxification of excess cyanide that may seep to the surrounding normal tissues. Thus properly administered by increasing the prodrug concentration at the tumor site and decreasing its systemic level, treatment of cancer using the relatively non-toxic linamarin, with or without the enzyme, linamarase could be a favoured future treatment for a variety of cancers.